2015
DOI: 10.1371/journal.pone.0116296
|View full text |Cite
|
Sign up to set email alerts
|

Risk Threshold for Starting Low Dose Aspirin in Pregnancy to Prevent Preeclampsia: An Opportunity at a Low Cost

Abstract: BackgroundPreeclampsia (PE) increases maternal and perinatal morbidity and mortality. Based on a multitude of data from randomized clinical trials, clinical practice guidelines endorse using ASA to prevent PE in women who are “at risk.” However, data are lacking about the level of absolute risk to warrant starting ASA prophylaxis.Methods and FindingsWe present two approaches for objectively determining the minimum absolute risk for PE at which ASA prophylaxis is justified. The first is a new approach—the minim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 29 publications
1
30
0
Order By: Relevance
“…17,18 Certainly, although we do not endorse use of ASA prophylaxis in all pregnant women and reiterate that the strategy should be focused at women at higher risk for preeclampsia and/or intra- uterine growth restriction, emerging data about ASA efficacy among women at differing risk may lead to a lowering of the threshold for starting ASA treatment. 22 The rate of preeclampsia and/or intrauterine growth restriction that we observed among all provider-initiated preterm births, 33.6%, is consistent with that noted by other investigators. 3,4 Morisaki and colleagues 31 found that, once preeclampsia or intrauterine growth restriction is present, avoidance of provider-initiated preterm birth is difficult, even when advanced obstetrical care is available.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…17,18 Certainly, although we do not endorse use of ASA prophylaxis in all pregnant women and reiterate that the strategy should be focused at women at higher risk for preeclampsia and/or intra- uterine growth restriction, emerging data about ASA efficacy among women at differing risk may lead to a lowering of the threshold for starting ASA treatment. 22 The rate of preeclampsia and/or intrauterine growth restriction that we observed among all provider-initiated preterm births, 33.6%, is consistent with that noted by other investigators. 3,4 Morisaki and colleagues 31 found that, once preeclampsia or intrauterine growth restriction is present, avoidance of provider-initiated preterm birth is difficult, even when advanced obstetrical care is available.…”
Section: Discussionsupporting
confidence: 92%
“…20,21 Moreover, although not currently recommended, ASA prophylaxis could be considered for all pregnant women who are not ASA intolerant, including those at low risk. 22 Given the low rate of ASA hypersensitivity in the general population, 23 we investigated the degree to which a universal ASA strategy might reduce rates of preeclampsia and intrauterine growth restriction and, thus, the number of provider-initiated preterm births. We further estimated how such reductions in provider-initiated preterm birth would affect maternal and newborn hospital length of stay.…”
mentioning
confidence: 99%
“…Iliac bone marrow was collected from the two healthy male volunteers aged 23 and 25, respectively. A histopaque-1077 density gradient was used for the separation, as previously described (14,15). The cells were cultured in MSC medium composed of Dulbecco's modified Eagle's medium (DMEM) low glucose (11885076; Thermo Fisher Scientific, Inc., Waltham, MA, USA,) supplemented with 10% fetal bovine serum (FBS; Thermo Fisher Scientific, Inc.) and 10 ng/ml basic fibroblast growth factor (Thermo Fisher Scientific, Inc.).…”
Section: Methodsmentioning
confidence: 99%
“…23,24 Current research is focused on the development of ASA therapy algorithms, as this is a low-cost, minimal risk oral medication. 25,26 However, ASA increases mean birth weight by only 130 g (the average amount lost by newborn infants when breastfeeding is established) and has no significant impact on perinatal mortality. 24 Despite ASA therapy, women continue to present in large numbers with the severe, early-onset PE, which is largely a placental-mediated disorder.…”
Section: Current Therapies For the Prevention And Treatment Of Pementioning
confidence: 99%